Unusual Cutaneous Reaction at Site of Methotrexate Injection in Two Patients with Psoriasis and Psoriatic Arthritis - Birgit Sadoghi; Birger Kränke; Lorenzo Cerroni; Wolfgang Weger (Medical Journals Sweden, 2021)
Abstract is missing (Short communication)